Getting published: Tips for emerging scholars - James Corcoran (Canadian Society for Studies in Education, 2015)
This editorial begins with discussion of the pervasive global demand for emerging scholars to achieve a record of publication in order to gain academic advancement. Following an overview of the myriad challenges emerging scholars face in achieving this publication, the editor describes the helping role of the CJNSE's open mentored review process in mediating some of these challenges. The editor then provides some quick tips to help emerging scholars with their production, submission, and revision of academic writing for publication. The final suggestion forwarded by the editor is for emerging scholars to become involved with the adjudication process as journals in their (sub)disciplinary area(s) in order to expedite their academic enculturation and connection to their desired discourse communities.